Elements of a shared theory of science for design - Per Galle (Artifact, 2018)

(untitled)
Abstract Higher education for the design professions – designers, architects and engineers – has been combining traditional disciplines of research and design in new ways, into what is now known as design research. As a discipline in its own right, design research is still quite young, and the design professions need a theory of science that takes their specific character into account, thus contributing to their self-image, and locating them in the greater landscape of research. Using philosophically oriented conceptual analysis I develop a system of basic concepts as elements of such a theory of science for the design professions. The concepts of design, research and design research are analysed, clarified and coordinated, in relation to concepts such as knowledge, theory and practice. At the same time I propose a precise, yet intuitive, terminology that may be shared and foster cross-disciplinary understanding and communication among the design professions, and which each of them can expand for purposes of its own.